Application of dielectric spectroscopy in an industrial bioprocess utilizing the baculovirus expression vector system - Brix, Alexander (Kansas State University, 2012)
Large-scale insect cell culture utilizing the baculovirus expression vector system (BEVS) can be used to produce biopharmaceuticals such as vaccines and therapeutic proteins. Biopharmaceutical production processes are generally complex and sensitive to many process parameters and changes, but on-line monitoring in this area is relatively limited and the fundamental understanding of the intricate relationships between significant process parameters and the process outcome, especially on the multi-liter or multi-m3 scale, is rarely conclusive. Dielectric spectroscopy (DS), which is based on the frequency dependent measurement of the passive dielectric properties of materials, was applied to large-scale insect cell cultures infected with a baculovirus under low multiplicity of infection conditions to produce a recombinant protein of the virus-like particle class. DS not only allowed the qualitative monitoring of the infection and recombinant protein production process within the culture in real-time but also the detection of important culture events, e.g. the peak in baculovirus production/concentration. Additionally, DS seemed to be able to serve as a predictive tool for the overall recombinant protein yield early in the process. Partial Least Square models were successfully developed allowing monitoring of the cultures progress in terms of cell density, size, and even nutrient concentration replacing the need for discrete sampling and therefore reducing contamination risks. In summary, DS has been demonstrated to have the potential to increase bioprocess understanding and the repeatability of recombinant protein production in the BEVS but ultimately also to satisfy the increased requirements for process monitoring as delineated recently in the Process Analytical Technology initiative by the Food and Drug Administration.
Keywords: Virus